2000
DOI: 10.1111/1469-8986.3760731
|View full text |Cite
|
Sign up to set email alerts
|

Motor and nonmotor event‐related potentials during a complex processing task

Abstract: Identification of the necessary stimulus properties to elicit the stimulus preceding negativity (SPN) has been the impetus for numerous research studies. The current study was conducted to explore the possibility that the SPN is an index of cognitive resource allocation. An auditory warning stimulus (S1) indicated whether an easy or difficult discrimination would occur at S2. The SPN was collected before a nonmotor discrimination task (S2) that consisted of identifying the higher of two bars. To eliminate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…If the SPN reflects attention, it should be larger in the difficult discrimination than in the easy discrimination. However, the actual SPN did not show an increase of amplitude as a function of stimulus discriminability whereas the P3 evoked by the same stimuli was affected by the discrimination difficulty (Hillman et al, 2000). Hillman et al concluded that the SPN is not an index of cognitive demand for a task.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…If the SPN reflects attention, it should be larger in the difficult discrimination than in the easy discrimination. However, the actual SPN did not show an increase of amplitude as a function of stimulus discriminability whereas the P3 evoked by the same stimuli was affected by the discrimination difficulty (Hillman et al, 2000). Hillman et al concluded that the SPN is not an index of cognitive demand for a task.…”
Section: Discussionmentioning
confidence: 90%
“…However, several studies suggested that attention is not directly related to the SPN. For example, studies using a stimulus discrimination task showed that the SPN amplitude in a difficult discrimination condition was not different (Hillman, Apparies, & Hatfield, 2000) or smaller (Kotani & Aihara, 1999) than that in an easy discrimination task. In the stimulus discrimination task, subjects have to pay more attention to stimuli when the stimulus discrimination is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of ERN‐like potentials, the response‐locked analysis revealed a different pattern of slow‐wave effects for rule violations and correct responses at parietal sites. Whereas this effect might resemble an error positivity for violation responses (P E ; Overbeek et al, ; Steinhauser & Yeung, ), it could also be interpreted as a stimulus‐preceding negativity for correct responses that has been observed in tasks involving feedback stimuli (Brunia, ; Hillman, Apparies, & Hatfield, ; van Boxtel & Böcker, ). Because the chicken in the current design laid an egg precisely 1,000 ms after stimulus onset, participants were able to anticipate this event that, on average, took place about 500–550 ms after their response (1,000 ms minus mean RT).…”
Section: Discussionmentioning
confidence: 99%
“…The possible utility of SPN in cue-reactivity studies appears especially promising because SPN has been related to neurobiological mechanisms underlying anticipation (Hillman et al, 2000;Kotani et al, 2003), arousal (Takeuchi et al, 2005), and motivation (Lang et al, 2005). Other potential advantages of the SPN paradigm are discussed here, along with how SPN might be combined with other electrocortical measures of cue reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…This measure is based on a design developed by Costell and colleagues to successfully differentiate sexual preference (Costell, Lunde, Kopell, & Wittner, 1972). Costell's design incorporated stimulus preceding negativity (SPN), a brain response that occurs during the anticipation of and motivation to attend to emotionally important stimuli (Hillman, Apparies, & Hatfield, 2000;Takeuchi, Mochizuki, Masaki, Takasawa, & Yamasaki, 2005). The older literature, including Costell's work, referred to SPN as a subtype of contingent negative variation that occurs between a cueing or warning stimulus (S1) and a motivationally or response-related second stimulus (S2) that occurs shortly (typically 1,000 ms to 4,000 ms) thereafter.…”
Section: Introductionmentioning
confidence: 99%